Integrasi Nilai-Nilai Islam dalam Pembelajaran Matematika SD/MI - Mimi Hariyani (Jurnal keilmuan dan Kependidikan dasar, 2013)
Nowadays, learning mathematics is still separated with Islamic religious education. Yet at the latest in madrasah curricu-lum requires the integration of Islamic values ​​in each subject. Integration of Islamic values ​​in the learning of mathematics itself is often considered difficult because teachers have not been accustomed to apply it. Actually, integrating Islamic values ​​into learning math is not difficult, it can be done in various ways such as: always mention the name of Allah, the use of the term, visual illustrations, or examples of applications, insert the relevant verse or hadith, search history, network topics, symbols kauniah verses